A new species of Pseudohalonectria from Thailand - Promputtha I. (2014)
Pseudohalonectria suthepensis sp. nov. isolated from dead leaves of Magnolia liliifera Baill. (Magnoliaceae) collected in Doi Suthep-Pui National Park, Chiang Mai, Thailand, is described and illustrated. The new species, which is compared with other species in the genus, differs in its longer ascospores.